PROSPECTS FOR DEVELOPMENT AND MAIN PROBLEMS OF THE CRYPTOCURRENCY MARKET - Eldarovich, Ishkuvatov Elyor (Journal of Contemporary Business Law & Technology: Cyber Law, Blockchain, and Legal Innovations, 2024)
This article examines cryptocurrency as the newest form of money, analyzing the main risks, trends, and prospects for its development. The advantages of cryptocurrency, such as decentralization, anonymity, and security, are also analyzed. However, serious risks related to price volatility and the lack of government regulation are also addressed. We analyze the main development trends in the cryptocurrency market, including the growth in the number of users and the increase in transaction volumes.